IMPLEMENTASI SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM PENINGKATAN PROFESIONALISME GURU - Selvia Selvia Selvia (UNIVERSITAS BENGKULU, 2015)
The general objective of this study was to describe the implementation of the academicsupervision of the principal in improving the professionalism of teachers in Junior High SchoolNumber 7 Seluma. This study uses evaluative. The subjects were the principal Junior High SchoolNumber 7 Seluma. Data were collected by using observation, interviews and documentation. Datawere analyzed descriptively. The results of this study indicate that the implementation of theacademic supervision of the principal in improving the professionalism of the teachersexecutedwith good.Keyword: academic supervision, principal,professionalism of teachers